EFEKTIVITAS PEER TEACHING TERHADAP PEMAHAMAN KETERAMPILAN MENGAJAR CALON GURU - Marcella Nurul Annisa; Nurina Asri Fitriani; Ossie Destiani Fadhilah; Syahid Musthofa Akhyar; Prihantini (STKIP Subang, 2023)
Currently, the challenges in the world of education are increasingly complex, requiring direct application of knowledge and skills for students as prospective teachers. Teaching skills are one of the keys to success in the learning process. For this reason, there needs to be learning that supports the development of knowledge and skills effectively. One way is through the implementation of peer teaching. Peer teaching is a forum for prospective teacher students to apply knowledge and practice skills regarding teaching skills. This research aims to evaluate the impact of peer teaching activities on students' understanding of teaching skills as prospective teachers. This research uses a qualitative descriptive research method. This research data was collected through literature review, interviews and observations. The results of this research show that the implementation of peer teaching can provide in-depth understanding for students as prospective teachers because, during its implementation students take turns being practitioners and observers. In the process, fellow student observers and lecturers provide constructive feedback regarding things that need to be improved in carrying out learning.